Economic‐environmental stochastic scheduling for hydrogen storage‐based smart energy hub coordinated with integrated demand response program - Agabalaye‐Rahvar, Masoud; Mansour‐Saatloo, Amin; Mirzaei, Mohammad Amin; Mohammadi‐Ivatloo, Behnam; Zare, Kazem (International journal of energy research, 2021)
Summary According to the necessity of establishing an effective, dependable, and cost‐effective system to supply various demands, the significance of an energy hub has emerged in recent years. Also, the other aspect dealing with decreasing the global warming issues should be taken into account. To this end, a smart multicarrier energy hub (SMEH) coordinated with an integrated demand response program (IDRP) and hydrogen storage system (HSS) as flexible resources has been proposed. Managing the consumption of electrical and thermal demands is handled by IDRP, whilst fuel cell–based HSS technology has an important role in lessening the air pollutant emissions. In reality, HSS could convert electrical power to hydrogen energy via power to hydrogen (P2H) at low price hours or in high renewable energy resources (RERs) penetrations; however, at high price periods or in low RERs penetrations, electricity is generated through hydrogen‐based fuel cells. In addition to the aforementioned parts, combined heat and power (CHP), boiler, gas‐fired units (GFUs), HSS, electrical heat pump (EHP), energy and thermal storage systems (ESS/TSS), and RERs are also considered in the SMEH. The scenario‐based stochastic method is utilized to handle the fluctuations of electricity price and RERs' output. The multiobjective scheduling framework of the problem is modeled as a mixed‐integer linear programming (MILP) to investigate and obtain the economic–environmental benefits. Consequently, the applicability of the introduced methodology is verified via sample case studies. Simulation outcomes represent that applying IDRP and HSS results in a decrement in overall cost and total emission by about 1.54% and 2.9%, respectively. According to the necessity of establishing an effective, dependable, and cost‐effective system to supply various demands, the significance of an energy hub has emerged in recent years. Also, the other aspect dealing with decreasing the global warming issues should be taken into account. To this end, a smart multicarrier energy hub (SMEH) coordinated with an integrated demand response program (IDRP) and hydrogen storage system (HSS) as flexible resources has been proposed